Modern Diagnostic Techniques for the Assessment of Ocular Blood Flow in Myopia: Current State of Knowledge - Grudzińska, Ewa (J Ophthalmol, 2018)
Myopia is the most common refractive error and the subject of interest of various studies assessing ocular blood flow. Increasing refractive error and axial elongation of the eye result in the stretching and thinning of the scleral, choroid, and retinal tissues and the decrease in retinal vessel diameter, disturbing ocular blood flow. Local and systemic factors known to change ocular blood flow include glaucoma, medications and fluctuations in intraocular pressure, and metabolic parameters. Techniques and tools assessing ocular blood flow include, among others, laser Doppler flowmetry (LDF), retinal function imager (RFI), laser speckle contrast imaging (LSCI), magnetic resonance imaging (MRI), optical coherence tomography angiography (OCTA), pulsatile ocular blood flowmeter (POBF), fundus pulsation amplitude (FPA), colour Doppler imaging (CDI), and Doppler optical coherence tomography (DOCT). Many researchers consistently reported lower blood flow parameters in myopic eyes regardless of the used diagnostic method. It is unclear whether this is a primary change that causes secondary thinning of ocular tissues or quite the opposite; that is, the mechanical stretching of the eye wall reduces its thickness and causes a secondary lower demand of tissues for oxygen. This paper presents a review of studies assessing ocular blood flow in myopes.